Changes in Social and Cultural Phenomena as a Result of Organizing the Sinar Harapan Village Open Volleyball Event - Prasetyo, Diko; Sulaiman, Sulaiman; Rustiadi, Tri (Journal of Physical Education and Sports, 2022)
This research is motivated by the sociocultural changes that have occurred in Sinar Harapan village as a result of the open volleyball sport event. This is a qualitative case study research design. The research collected data from Youth Organizations, Village Leaders, and the community. Techniques for data collection include observation, interviewing, and documenting. Data analysis was composed of four interdependent components data gathering, data reduction, data visualization, and conclusion. The findings of this study were the social conditions of the Sinar Harapan village community. Currently, the village community's primary source of income is farming, but some members work as workers. Community interaction is strong due to collaborative sports activities in the village. Sinar Harapan village's cultural conditions for the majority of Javanese tribes the daily routine of farming and activities conducted by youth and community members every afternoon in the village field. Discussions have begun to take place frequently in the village in order to invite the community to participate in village building activities. The positive impact of holding an open volleyball event in Sinar Harapan village is that the community learns that sports are not only beneficial to health but can also bring together many ethnic groups, ethnicities, and religions through sports interactions. The negative impact is that some people still gamble during volleyball matches. The investigation concludes that the village community's culture is evolving, and members are now routinely participating in sports on the sidelines of their work the community feels motivated to exercise and support village activities.